2000
DOI: 10.1155/s1064744900000053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Postpartum Endometritis and Wound Infection

Abstract: Awareness of the aforementioned associations may prevent and shorten hospital stay by early diagnosis and appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 0 publications
1
11
1
2
Order By: Relevance
“…Shehla et al (21) had reported the incidence of puerperal pyrexia as 44.7% and Jolly et al (16) as 7.58%. Incidence of wound infection had been reported as 6% by Chaim et al (30) and 2% by Andrews et al (31) Incidence of Chorioamnionitis had been reported as 4% by Hannah et al (2) and 1.6% by Ottervanger et al (32) In our study, significant number of neonates (27.6%) required NICU observation for mild respiratory distress and 5.3% of neonates were admitted in NICU for perinatal asphyxia and 2.6% of neonates were admitted for neonatal sepsis. There were no perinatal deaths.…”
Section: Discussionsupporting
confidence: 48%
“…Shehla et al (21) had reported the incidence of puerperal pyrexia as 44.7% and Jolly et al (16) as 7.58%. Incidence of wound infection had been reported as 6% by Chaim et al (30) and 2% by Andrews et al (31) Incidence of Chorioamnionitis had been reported as 4% by Hannah et al (2) and 1.6% by Ottervanger et al (32) In our study, significant number of neonates (27.6%) required NICU observation for mild respiratory distress and 5.3% of neonates were admitted in NICU for perinatal asphyxia and 2.6% of neonates were admitted for neonatal sepsis. There were no perinatal deaths.…”
Section: Discussionsupporting
confidence: 48%
“…Comparisons for categorical variables were performed using the 2 or Fisher exact test. Continuous variables were compared using the Student t or Mann-Whitney U tests.…”
Section: Discussionmentioning
confidence: 99%
“…1 The rates of SSI after cesarean section reported in the literature range from 3% to 15%, depending on the surveillance methods used to identify infections, the patient population, and the use of antibiotic prophylaxis. [2][3][4][5][6][7][8][9][10][11] The pooled mean rate of SSI after cesarean section for US hospitals participating in the Centers for Disease Control and Prevention's National Nosocomial Infections Surveillance System is 3.15%. 12 Expanding our knowledge of the risk factors associated with SSI is essential to developing targeted prevention strategies to reduce the risk of SSI.…”
Section: Infect Control Hosp Epidemiol 2008; 29:477-484mentioning
confidence: 99%
“…4,6,7 The rates of SSI after CS reported in the literature ranges from 3% to 15%, depending on the surveillance methods used to identify infections, the patient population, and the use of antibiotic prophylaxis. 8,9 The risk factors for SSI in association with cesarean section are many, including those case-mix issues present in the surgical patient population such as age, factors such as type of CS (elective vs emergency), and patient care practices such as antibiotic prophylaxis. Analysis of the combined effects of the intrinsic and extrinsic risk factors predisposing patients to SSI is necessary to detect the common links.…”
Section: Introductionmentioning
confidence: 99%